2015
DOI: 10.18488/journal.62/2015.2.4/62.4.100.119
|View full text |Cite
|
Sign up to set email alerts
|

The Total Factor Productivity of Libyan Banks, 2004 – 2010

Abstract: This paper provides a comparative analysis regarding the performance of 17 Libyan banks over the period 2004 up to 2010. According to the relevant literature, there are few studies that measure both technical efficiency and Malmquist productivity index approach using non -parametric approach (DEA) for the banking sector in Libya. For this study, the DEA technique was used to estimate technical, pure technical, and scale efficiency of sampled banks by using DEAP software. . The results showed that the specializ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…In other words, profitable banks use their assets and resources efficiently, which is why they will earn more profit. This result is consistent with the previous studies of Isik and Hassan (2002), Casu and Molyneux (2003), Hasan and Marton (2003), and Alrafadi (2015).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…In other words, profitable banks use their assets and resources efficiently, which is why they will earn more profit. This result is consistent with the previous studies of Isik and Hassan (2002), Casu and Molyneux (2003), Hasan and Marton (2003), and Alrafadi (2015).…”
Section: Resultssupporting
confidence: 94%
“…In this study, Ray (2007) also suggested that the State Bank of India is too large and should be broken up into more than 25 smaller banks. An increase in the size of banks is a source of additional costs, which tends to reduce the efficiency of the large banks (Alrafadi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations